Analgesic and anti-inflammatory properties of essential oil from Ageratum fastigiatum - Glauciemar Del-Vechio-Vieira; Orlando Vieira de Sousa; Mariza Abreu Miranda; Luci Senna-Valle; Maria Auxiliadora Coelho Kaplan (Brazilian Archives of Biology and Technology, 2009)
The chemical composition, analgesic and anti-inflammatory properties of essential oil from Ageratum fastigiatum were investigated. The main compounds found in the essential oil were germacrene D, α-humulene and β-cedrene. The oil, with LD50 of 2.50 g/kg, inhibited the acetic acid-induced writhing at the dose of 200 mg/kg. In the formalin test, the oil inhibited the first phase (200 mg/kg) and the second phase (100 mg/kg and 200 mg/kg). In the hot plate test, after 30 and 60 min of treatment the doses of 100 and 200 mg/kg increased the reaction time. The antiedematogenic effect, reduction on the exudate volume and leukocyte mobilization were observed at the doses of 100 and 200 mg/kg. The results indicated that A. fastigiatum possessed the analgesic and anti-inflammatory properties that supported the popular medicinal use of the plant. A composição química e as propriedades analgésica e antiinflamatória do óleo essencial de Ageratum fastigiatum foram investigadas. Os principais constituintes do óleo essencial foram germacreno D, α-humuleno e β-cedreno. O óleo, com DL50 de 2,50 g/kg, inibiu as contorções abdominais induzidas por ácido acético na dose de 200 mg/kg. No teste da formalina, o óleo inibiu a primeira fase (200 mg/kg) e a segunda fase (100 e 200 mg/kg). O tempo de latência aumentou no teste da placa quente, após 30 e 60 minutos de tratamento, nas doses de 100 e 200 mg/kg. O efeito antiedematogênico, assim como a redução do volume do exsudato e da migração leucocitária foram observados nas doses de 100 e 200 mg/kg. Os resultados indicam que o A. fastigiatum possui propriedades analgésica e antiinflamatória, o que corrobora com o uso popular da planta.